Physics, chemistry and applications of nanostructures : reviews and short notes. Proceedings of International Conference Nanomeeting 2015, Minsk, Belarus, 26-29 May 2015 - Borisenko, V. E.; Gaponenko, S. V. 1958-; Gurin, V. S.; Kam, C. H. (World Scientific Publishing, 2015)
"This book presents invited reviews and original short notes of recent results obtained in studies concerning the fabrication and application of nanostructures, which hold great promise for the new generation of electronic, optoelectronic and energy conversion devices. They present achievements discussed at Special Sessions "Frontiers of Two-Dimensional Crystals", "Nanoelectromagnetics" and Belarus-Korea Workshop "Frontiers of Advanced Nanodevices" organized within Nanomeeting 2015. Governing exciting and relatively new topics such as fast-progressing nanoelectronics and optoelectronics, molecular electronics and spintronics, nanophotonics, nanosensorics and nanoenergetics as well as nanotechnology and quantum processing of information, this book gives readers a more complete understanding of the practical uses of nanotechnology and nanostructures."--